Acute-serum amyloid A and A-SAA-derived peptides as formyl peptide receptor (FPR) 2 ligands - Abouelasrar Salama, Sara; Gouwy, Mieke; Van Damme, Jo; Struyf, Sofie (Frontiers in Endocrinology, 2023)
Originally, it was thought that a single serum amyloid A (SAA) protein was involved in amyloid A amyloidosis, but in fact, SAA represents a four‐membered family wherein SAA1 and SAA2 are acute phase proteins (A-SAA). SAA is highly conserved throughout evolution within a wide range of animal species suggestive of an important biological function. In fact, A-SAA has been linked to a number of divergent biological activities wherein a number of these functions are mediated via the G protein-coupled receptor (GPCR), formyl peptide receptor (FPR) 2. For instance, through the activation of FPR2, A-SAA has been described to regulate leukocyte activation, atherosclerosis, pathogen recognition, bone formation and cell survival. Moreover, A-SAA is subject to post-translational modification, primarily through proteolytic processing, generating a range of A-SAA-derived peptides. Although very little is known regarding the biological effect of A-SAA-derived peptides, they have been shown to promote neutrophil and monocyte migration through FPR2 activation via synergy with other GPCR ligands namely, the chemokines CXCL8 and CCL3, respectively. Within this review, we provide a detailed analysis of the FPR2-mediated functions of A-SAA. Moreover, we discuss the potential role of A-SAA-derived peptides as allosteric modulators of FPR2.